THE EFFECTS OF PRECOCIOUS AGING: A LITERATURE SURVEY (Fiep Bulletin - online, 2011)
For constituting a long period of existence, the stage of aging collects besides life experiences, also the physical and mental effects on the individual. This stage comprehends the accumulation of experiences that often may have been healthy or not. On that aspect, we emphasize the aging precocious, whether it is due to quality of life or even pathological, as in the case of Progeria. The aging precocious results from numerous causal factors that affects the individual throughout its existence, assuming the character of various degrees in different intensities. It is unbalanced molecules that facilitate the aging precocious of the whole body. The change occurs by factors such as lifestyle, habits, genetics, and diseases resulting from or by the approach given to him by the disease. The multidisciplinary approach of this phase is to work for a better understanding of their expressions in the life of every individual, who for one reason or another, come to victimize from this amendment or know people who pass through it in order to explain, clearly, one subject little commented on health, because many areas approach him addressing the aesthetic issues, limiting the overview of this condition.
Keywords: Effects; Precocious aging; Multidisciplinary